Endoplasmic Reticulum Stress and Impairment of Ribosome Biogenesis Mediate the Apoptosis Induced by Ocimum x africanum Essential Oil in a Human Gastric Cancer Cell Line - Wongwarut Boonyanugomol (2022)
Background and Objectives: Gastric cancer remains a major unmet clinical problem worldwide. Although conventional medical treatments are available, their curative effects are generally unsatisfactory. Consequently, it remains necessary to search natural products for potential alternatives in treating gastric cancer patients. Ocimum x africanum Lour. is a culinary herb that has been used in folk medicine for various diseases, but little is known regarding its anti-cancer activity against gastric cancer cells. In the current study, we focus on the anti-cancer mechanisms of O. x africanum essential oil (OAEO) in the AGS human gastric cancer cell line. Materials and Methods: After OAEO treatment, AGS cell viability was evaluated by MTT assay. Cell migration and apoptotic nuclear morphology were determined by wound-healing assay and DAPI staining, respectively. Gene expression levels of apoptosis-related genes were quantified by qRT–PCR. Differential protein expression was determined with an LC–MS/MS-based proteomics approach to identify the key proteins that may be important in the anti-cancer mechanisms of OAEO on AGS cells. The chemical constituents of OAEO were identified by GC–MS analysis. Results: We found OAEO to exhibit a potent growth-inhibiting effect on AGS cells, with an IC50 value of 42.73 µg/mL. After OAEO treatment for 24 h, AGS cell migration was significantly decreased relative to the untreated control. OAEO-treated AGS cells exhibited common features of apoptotic cell death, including cell shrinkage, membrane blebbing, chromatin condensation, and nuclear fragmentation. Apoptotic cell death was confirmed by qRT–PCR for apoptosis-related genes, revealing that OAEO decreased the expression of anti-apoptotic genes (BCL2 and BCL-xL) and activated pro-apoptotic genes and apoptotic caspase genes (TP53, BAX, CASP9, CASP12, and CASP3). Moreover, expression of CASP8 was not changed after treatment. Proteomic analysis revealed that OAEO may produce a signature effect on protein clusters relating to unfolded protein accumulation, thereby inducing severe ER stress and also impairing ribosome synthesis. STRING analysis revealed seven up-regulated and 11 down-regulated proteins, which were significantly associated with protein folding and ribosome biogenesis, respectively. Using GC–MS analysis, 6-methyl-5-hepten-2-one, citral, neral, and linalool were found to be the major chemical constituents in OAEO. Conclusions: Taken together, these results indicate that OAEO has a potential anti-proliferative effect on AGS cells. Our molecular findings show evidence supporting an important role of ER stress and ribosome biogenesis impairment in mediating the induction of cell death by OAEO through the mitochondrial-apoptotic pathway. This study, therefore, provides fundamental knowledge for future applications using OAEO as an alternative therapy in gastric cancer management.